2020
DOI: 10.1017/s071498082000029x
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Fidelity of a Volunteer-Led Montessori-Based Intervention in a Canadian Long-Term Care Home

Abstract: Montessori-based interventions (MBIs) were developed to promote guided participation in meaningful activities by people with dementia patients. In this study, we assessed nursing home volunteers’ fidelity to an MBI, relying primarily on a qualitative descriptive design. We completed a deductive content analysis of eight volunteer interviews using the Conceptual Framework for Intervention Fidelity. We also calculated average volunteer and resident scores on the Visiting Quality Questionnaire (VQQ), which assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Hunter et al 16 . assigned nine community volunteers to deliver a Montessori‐based intervention (MBI), an intervention which consists of practical, sensorial, cognitive, and sociocultural domains that emphasize the participation of people with dementia in meaningful activities according to their interests.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hunter et al 16 . assigned nine community volunteers to deliver a Montessori‐based intervention (MBI), an intervention which consists of practical, sensorial, cognitive, and sociocultural domains that emphasize the participation of people with dementia in meaningful activities according to their interests.…”
Section: Resultsmentioning
confidence: 99%
“…Adherence to the MBI and associated moderators was measured by interviews and using the Visiting Quality Questionnaire (VQQ), with scores of satisfied/good quality for the visits on the Resident Response subscale and very satisfied/high‐quality for the visits on the Volunteer Response subscale. They also suggested that volunteers working with older people who have late‐stage dementia receive additional support, for example preparing them with information about late‐stage dementia, training in non‐verbal communication and intervention skill modelling 16 …”
Section: Resultsmentioning
confidence: 99%
“…Qualitative evidence also highlighted the importance of reciprocal relationships with residents to help volunteers feel appreciated and to recognise that their visits were beneficial (Lokon et al., 2012; Persson, 2004; Tanner & Brett, 2014). However, when volunteers felt they were unable to engage residents or encourage them to participate in activities, this could leave them feeling frustrated (Hunter et al., 2021; Keith, 2003; Lokon et al., 2012; Van der Ploeg et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Volunteers felt more efficacious in their work, and more supported by staff when they were treated as part of the care team. Previous research has shown that volunteers consider staff support and volunteer training to be important (Hunter, Rissling, et al, 2020;McDonnell et al, 2014). Additionally, support and training have been found to be associated with reduced emotional distress, potential burnout, and dropout rates among volunteers (Chung, 2009;Hurst et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Role clarification is an important initial step for supporting relationships between staff and volunteers ( Hande et al., 2021 ; Hurst et al, 2019 ). With adequate role development and support, long-term care staff may be enthusiastic about the contributions of volunteers, recognizing the benefits to residents and to their own work ( Hunter, Rissling, et al., 2020 ; Hurst et al, 2019 ).…”
mentioning
confidence: 99%